Microsoft’s Strategic Transformation through Data Center Development in Indonesia - Hapsari, Karina Erdian; Hakiki, Falhan (Global Strategis, 2026)
The Covid-19 pandemic has benefitted technology corporations due to the urgent need for large-scale digital transformation. Microsoft, for instance, collaborated with the Indonesian government in the development of its first data center in the country. This case is particularly notable, as Microsoft was able to assert its presence amid the uncertainty caused by the pandemic. This qualitative approach uses the main theory of corporate-state alliance and technology-driven as supporting theory to demonstrate the need for both actors to survive in the pandemic era and the shift in Microsoft’s development. Two key findings emerge. First, there is a balance of needs between the two actors. Second, there is an economic variable. The balance of needs reflects the equally strong positions of the state and the corporation, while the economic variable refers to the mutual economic benefits gained by both parties. This article concludes that the crisis could be a “turning point” for Microsoft and the Indonesian government to achieve greater profits, particularly in terms of business potential compared to normal situations.Keywords: Corporate-State Alliance, Covid-19 Pandemic, Microsoft, Indonesian Government, Data Center Development Pandemi Covid-19 telah menguntungkan korporasi yang bergerak di bidang teknologi karena kebutuhan mendesak akan transformasi digital secara masif. Microsoft, misalnya, bekerja sama dengan pemerintah Indonesia terkait dengan pembangunan pusat data pertama di Indonesia. Hal tersebut cukup unik karena Microsoft mampu menunjukkan eksistensinya dalam ketidakpastian akibat pandemi. Tulisan dengan pendekatan kualitatif ini menggunakan teori utama aliansi korporasi-negara dan teori technology driven sebagai pendukung untuk menunjukkan adanya kebutuhan bertahan kedua aktor di era pandemi serta adanya pergeseran perkembangan Microsoft. Terdapat dua temuan penting, yaitu pertama, ada keseimbangan kebutuhan kedua aktor dan kedua, adanya variabel ekonomi. Keseimbangan kebutuhan korporasi-negara menggambarkan posisi kedua aktor tersebut yang sama kuat. Sementara itu, variabel ekonomi mengarah pada keuntungan ekonomi yang diperoleh kedua pihak. Tulisan ini berkesimpulan bahwa situasi krisis bisa menjadi “titik poin” bagi Microsoft dan pemerintah Indonesia untuk mendapatkan keuntungan lebih, khususnya dalam potensi bisnis dibandingkan saat situasi normal.Kata-kata Kunci: Aliansi Korporasi-Negara, Pandemi Covid-19, Microsoft, Pemerintah Indonesia, Pembangunan Pusat Data